Effect of expired pharmaceutical dumping on ecological community - Dipanshu Kumar Vishwas (Wolters Kluwer Medknow Publications, 2022)
Most people usually throw unused or expired medicines at open landfill sites or isolated locations completely inadvertently due to the consequences and lack of drug disposal facilities. Thus, our field of investigation focuses on whether disposal medicine has any direct effect on various life forms, including humans. This investigation describes how medicinal metabolites develop through wastewater that continuously enters the aquifer and soil environment. Since the discharge of toxic drugs has antibacterial activity, loss of soil fertility, aquatic species have a feminizing effect in males, and bioaccumulation affects inland animals including humans promote global consequences, and thus food affects the chain. Thus, a review of this study might furnish a good conception on the issue of lapsed pharmaceutical wastage and its effect on biological networks. The work concludes with better knowledge about the current conditions of drug wastage around the world, including India, and how biologically active ingredients can have devastating effects on the metabolism of various life forms in the ecological community. This article can also be very useful for understanding, aware and cautioning about the future consequences of drugs by people carelessly in the environment, and turning the brain to the urgent need for a strict and complete proof policy on its safe dumping so that its harmful effects on the environment can be minimized.